Adaptation Strategy of Hotel Management to Face National Financial Efficiency Policy: Evidence Based from Lombok, Indonesia - Anak Agung Ngurah Sedana Putra; Putu Ari Nugraha; M. Ihdal Karomi (Indonesian Journal of Tourism and Leisure, 2026)
This study examines the impact of national financial efficiency policies on the performance of the hospitality industry in Lombok and explores how hotel management adapts to these fiscal pressures. It also analyzes regional variations and identifies strategic responses to sustain business performance. A qualitative approach with a multiple case study design was employed across Mataram City, West Lombok, North Lombok, East Lombok, and Central Lombok. Data were collected through in-depth interviews, field observations, and analysis of operational and marketing documents, and were analyzed using thematic and cross-regional comparative techniques. The findings reveal that financial efficiency policies significantly affect hotels highly dependent on the government Meetings, Incentives, Conferences, and Exhibitions (MICE) segment, particularly in administrative areas such as Mataram City. In contrast, hotels oriented toward leisure markets, international tourists, and experience-based models demonstrate greater resilience. The study highlights that market diversification, marketing repositioning, digitalization, operational efficiency, and adaptive revenue management are critical strategies for enhancing resilience. These results suggest the need for a paradigm shift from reliance on public spending toward more flexible, market-oriented, and sustainable business models in response to evolving national economic policies.